Memory and community in sixteenth-century France - LaGuardia, David P.; Yandell, Cathy M. (Ashgate Publishing, 2015)
"Memory & Community in Sixteenth-Century France engages the question of remembering from a number of different perspectives. It examines the formation of communities within diverse cultural, religious, and geographical contexts, especially in relation to the material conditions for producing texts and discourses that were the foundations for collective practices of memory. The Wars of Religion in France gave rise to numerous narrative and graphic representations of bodies remembered as icons and signifiers of the religious 'troubles.' The multiple sites of these clashes were filled with sound, language, and diverse kinds of signs mediated by print, writing, and discourses that recalled past battles and opposed different factions. The volume demonstrates that memory and community interacted constantly in 16th-century France, producing conceptual frames that defined the conflicting groups to which individuals belonged, and from which they derived their identities. The ongoing conflicts of the Wars hence made it necessary for people both to remember certain events and to forget others. As such, memory was one of the key ideas in a period defined by its continuous reformulations of the present as a forum in which contradictory accounts of the recent past competed with one another for hegemony. One of the aims of Memory and Community in Sixteenth-Century France is to remedy the lack of scholarship on this important memorial function, which was one of the intellectual foundations of the late French Renaissance and its fractured communities"--Provided by publisher